Czy wolno się śmiać na wojnie? Wokół warszawskiej kariery teatru „Drugiego nurtu” w latach 1914–1918 (oczami wybranych satyryków i krytyków literackich) - Niewiarowska, Joanna (Załącznik Kulturoznawczy, 2020)
The article is dedicated to the phenomenon of development of the ‘second current’ theater (popular and music hall scenes) in the years 1914–1918. Having remained unexplored until now, the phenomenon has been analyzed in view of its perception (statements of literary critics, journalism, memories of authors of cabaret scenes), primarily interpreted against the background of various theories of laugh, comedy and cabaret (Bergson, Eco, Fleischer, Simmel, Żygulski). The main thesis of the article is that cabaret work developed in contrast to official war culture and performed not only the compensatory function, but also guaranteed a cultural promotion for new receivers and created new experience for communities. In this way it contributed to the democratization of culture and enhanced the processes of differentiation of literary circulation. By creating a discursive space of liminal character, it facilitated the emergence of new patterns of behavior (including political and civic ones) as well as new kind of social bonds, characteristic of the Polish culture in the interwar period.